Hubungan Pengetahuan Remaja dengan Perilaku SADARI sebagai Deteksi Dini Kanker Payudara di SMAS Muhammadiyah Kabupaten Mukomuko - Reditta Hasugian; Murwati Murwati; Yesi Putri (Utami Publisher, 2026)
Breast cancer ranks first in terms of the highest number of cancer cases in Indonesia and is one of the leading causes of cancer deaths. According to Globocan data for 2020, the number of new breast cancer cases reached 68,858 cases (16.6%) of the total 396,914 new cancer cases in Indonesia. Meanwhile, the number of deaths reached more than 22,000 cases (Indonesian Ministry of Health, 2022). The purpose of this study is to determine a correlation between adolescents' knowledge and SADARI behavior as early detection of breast cancer at SMAS Muhamadiyah, Mukomuko Regency. This study used an analytical research design with a cross-sectional study. Variable measurements were taken at a single point in time, meaning that subjects were observed and measured at the same time. Sampling was conducted using the total sampling method. The sample size for this study was 39 female students at SMAS Muhamadiyah in Mukomuko Regency. The results of the study showed that the frequency distribution of respondents with good knowledge was 19 (48.7%) and respondents with good SADARI behavior was 23 (59.0%). The Chi-square test results showed that the variable of Knowledge Level was related to SADARI behavior with a Chi-square p-value of 0.001 (α<0.05), so it can be concluded that there is a correlation between the knowledge level of adolescent girls with SADARI behavior as Early Detection of Breast Cancer at SMAS Muhamadiyah, Mukomuko Regency. The conclusion of the study is that there is a correlation between knowledge level and SADARI behavior as early detection of breast cancer. It is recommended that schools collaborate with health service institutions and community health centers to increase adolescent girls' knowledge about SADARI.